EFIKASI DOSIS PUPUK TEPUNG TULANG (TULAG SAPI DAN TULANG AYAM) TERHADAP PERTUMBUHAN TANAMAN SORGHUM (Sorghum bicolor, (L) MOENCH) PADA TANAH PMK - Sri Utami Lestari (Universitas Lancang Kuning, 2015)
ABSTRACT Sorghum has the advantage on agroecology broad adaptability, resistant to drought, higher production, and greater resistance to pests and diseases than other food crops. In addition to food substitution of sorghum utilization can also be used as a raw material source of alternative energy, namely as a fertilizer industry bioethanol.Dengan the bones of calcium and magnesium in the soil can be supplied and is also expected to increase the soil pH. The purpose of this study was to determine the effect and get a good dose of fertilizer tlang on the growth of sorghum. Research conducted an experiment with completely randomized design consisting of 4 levels treatments and 3 replications. S0 = Without treatment (control), S1 = Giving bone meal 5 g / plant, S2 = Giving bone flour 10 gr / plant, S3 = Giving bone flour 15 gr / plant. Data were analyzed using analysis of variance if F count ≥ F tables at the level of 5%, then followed by a further test Duncans. The results Award bone meal no real effect on all parameters of plant growth (plant height, leaf width and leaf length), results showed an increasing trend of numerical results with increasing dose given bone meal.